Jervell and Lange-Nielsen Syndrome in deaf school children population - Farrukh, Huma; Khushdil, Arshad; Saleem, Farrukh; Ehsan, Azra (Journal of Postgraduate Medical Institute, 2013)
Objective: To identify the patients of Jervell and Lange-Nielsen syndrome (JLNS) amongst congenitally deaf children. Methodology: This was a cross-sectional study, conducted at Hamza Foundation Academy for the Deaf,and Combined Military Hospital Lahore over a period of 4 months from February to May 2012. A totalof 379 children with congenital sensorineural hearing loss were included in this study. Echocardiographsof all children (ages 4-18 years) were obtained. The corrected QT (QTc) intervals of all 379 ECGs werecalculated using the Bazett's formula. Using the Schwartz's criteria, patients with long QTc intervals werefurther evaluated for Jervell and Lange-Nielsen Syndrome. Results: Out of 379 children, 84 (22.1%) were found to have QTc intervals equal to or longer than 0.44seconds. As per Schwartz's criteria, 31 (36.9%) out of 84 children with Long QTc (8.17% in sample population),scored high points (4.0 to 6.0), proving presence of JLNS. Conclusion: A sizable proportion of congenitally deaf children had Jervell and Lange-Nielsen Syndromein our study.